ANALISIS KEMAMPUAN SPASIAL SISWA KELAS VIII DALAM MEMECAHKAN MASALAH GEOMETRI DITINJAU DARI GAYA BELAJAR - Uswatun Hasanah Iriani; Venissa Dian Mawarsari; Iswahyudi Joko Suprayitno (Journal of Lesson Study in Teacher Education, 2024)
This study aims to describe the spatial abilities of students with visual, auditory, and kinesthetic learning styles. The type of research used in this study is qualitative descriptive research. The research subjects consisted of 21 students in class VIII, MTs Al Hidayah Sadeng, Semarang. Data collection techniques include tests, anchors, and interviews. The results of this study showed that students with high spatial and moderate visual and auditory learning styles were able to understand the problem by explaining what was known and being asked correctly. And it's able to relate concepts so that it can find the right formula and solve the given problem correctly and precisely. Meanwhile, students with moderate abilities and a kinetic learning style are only able to write down what is known and asked. And yet it has not been able to relate concepts so that it cannot find the right formula and not solve the given problem properly and precisely. While students with low spatial abilities with visual and kinesthetic learning styles are able to write down what is known and asked, subjects with auditory learning styles write but are less precise. Students with visual, auditory, and kinesthetic learning styles have not been able to relate concepts, so they have not been able to find the right formula and cannot solve the given problem correctly and precisely. Students with high spatial, medium, or low abilities cannot describe objects based on what is known and asked.